HUBUNGAN PENGETAHUAN NYERI HAID TERHADAP PENGGUNAAN JAMU TRADISIONAL KUNYIT ASAM PADA REMAJA DI DESA DANGIN PURI KELOD - Savitri, Devi (Bali International Scientific Forum, 2022)
Menstrual pain can interfere with the activities of young women in their activities. The prevalence of menstrual pain in Indonesia is 64.25% consisting of 54.89% primary menstrual pain and 9.36% secondary menstrual pain. Based on the incidence of menstrual pain in Bali is estimated at 29,505 people. Among the 29.505 people, some experienced secondary dysmenorrhea pain, some experienced primary dysmenorrhoea pain and ranging from mild to severe dysmenorrhoea. The prevalence of menstrual pain found in one study in Denpasar City was 74.42%. Purpose: This study was to determine the relationship between knowledge of menstrual pain and the use of traditional herbal medicine turmeric acid in adolescents in the village of Dangin Puri Kelod. Metfhod: This study is a non-experimental study, with a cross-sectional design. The research time is from March to May 2022. Data analysis using the Spearman Rank test. The sample used in this study were 100 people using the Non-Probability Sampling method with purposive sampling technique. With the inclusion criteria that have been determined. Results: The results of this study indicate that there is a significant relationship between knowledge and the use of traditional herbal medicine turmeric acid in adolescents as indicated by the P-value of the Spearman Rank test (0.001) < (0.05). With a Correlation Coefficient value of 0.221 which is included in a positive correlation with a correlation located in the range of 0.20 – 0.399, it can be concluded that it has a low relationship. Conclusion: If the level of knowledge of adolescents regarding menstrual pain is good, then the use of traditional herbal medicine turmeric acid will also be better.